2008
DOI: 10.1186/1746-4269-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health conditions treated with traditional and biomedical health care in a Quechua community in rural Bolivia

Abstract: Background: The objective of the present study was to reveal patterns in the treatment of health conditions in a Quechua-speaking community in the Bolivian Andes based on plant use data from traditional healers and patient data from a primary health care (PHC) service, and to demonstrate similarities and differences between the type of illnesses treated with traditional and biomedical health care, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 26 publications
10
96
2
5
Order By: Relevance
“…There are numerous reports in the literature of the use of industrialized medicines in association with natural products (Calvet-Mir et al, 2008;Shin et al, 2008;Vandebroek, et al, 2008), as well as evidence that animal and plant products can modulate the effects of commercial medicines by increasing or reducing their efficiency (Coutinho et al, 2008;Santos et al, 2012a,b). Table 3 presents the results of the association of ORJ in sub-inhibitory concentrations (MIC/8) with antifungal agents (mebendazol, amphotericin B, nystatin, and benzoilmetronidazole) against species of Candida.…”
Section: Constituentsmentioning
confidence: 99%
“…There are numerous reports in the literature of the use of industrialized medicines in association with natural products (Calvet-Mir et al, 2008;Shin et al, 2008;Vandebroek, et al, 2008), as well as evidence that animal and plant products can modulate the effects of commercial medicines by increasing or reducing their efficiency (Coutinho et al, 2008;Santos et al, 2012a,b). Table 3 presents the results of the association of ORJ in sub-inhibitory concentrations (MIC/8) with antifungal agents (mebendazol, amphotericin B, nystatin, and benzoilmetronidazole) against species of Candida.…”
Section: Constituentsmentioning
confidence: 99%
“…Thus the concept of health is not taken only as a state of absence of disease. Some periods are considered at risk or imbalance of the body, such as pregnancy (MeyerRochow 2009), menstrual cycle (Herndon et al 2009), childbirth and puerperium (Vandebroek et al 2008) that also deserve attention.…”
Section: Resultsmentioning
confidence: 99%
“…Vandebroek et al (2008) revealed patterns in the treatment of health conditions nesta community based on plant use data from traditional healers and patient data from a primary health care (PHC) service, and to demonstrate similarities and differences between the type of illnesses treated with traditional and biomedical health care, respectively. Meyer-Rochow (2009) found that many taboos affect pregnant women and are largely related to the fields of mind and "psyche".…”
Section: Resultsmentioning
confidence: 99%
“…Traditional medicine is an important cultural tradition in the Andes (Bastien 1987a ;Vandebroek et al 2004bVandebroek et al , 2008 and continues to occupy a central role in the daily lives of many rural and urban Andean peoples (Sikkink 2000 ;De Feo 2003 ;Finerman and Sackett 2003 ;Macia et al 2005 ;Vidaurre de la Riva 2006 ;Cerón 2006 ;De-laCruz et al 2007 ;Vandebroek et al 2008 ) . Several studies have shown that even though accessibility to Western medicine has increased considerably for rural Andeans, they are still highly dependent on traditional medicine Vandebroek et al 2004aVandebroek et al , 2008 .…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown that even though accessibility to Western medicine has increased considerably for rural Andeans, they are still highly dependent on traditional medicine Vandebroek et al 2004aVandebroek et al , 2008 . Based on household interviews, Vandebroek et al ( 2004a ) have demonstrated that despite the presence of a primary health care center (PHC) in the village, people from the rural Bolivian Andean community of Apillapampa still rely heavily on medicinal plants and not pharmaceuticals of industrial origin for their healthcare.…”
Section: Introductionmentioning
confidence: 99%